Faktor-faktor yang mempengaruhi niatan migran untuk menetap di Kota Jambi - Fera Diana; Junaidi Junaidi; Jaya Kusuma Edi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
This study aims to: 1) Identify the conditions of migrants in Jambi City, and 2) Analyze the factors that influence the intention of migrants to stay in Jambi City. The method used in this study is quantitative descriptive, using primary data obtained by interview. Based on the identification of 98 respondents, they were dominated by migrants with male sex aged 20-29 years, were married and lived in a contract/ rent house. Estimated results of Binary Logistic Regression, simultaneously shows a significant influence between the intention of migrants to stay in Jambi City with the variables in the model. While partially, the intention of migrants to stay in Jambi City is influenced by gender variables, higher education level variables, marital status variables, home ownership status variables and income variables. Age variable, high school / equivalent education level variable and variable workplace distance from the origin region is not significant to the intention of migrants to stay in Jambi City.